PENGARUH MANAJEMEN LABA, GOOD CORPORATE GOVERNANCE, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP KINERJA KEUANGAN PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BEI - Riskasari, Annisa; Witono, Banu (LPPM Universitas Bina Bangsa, 2024)
The research aims to examine the influence of Earning Management, Good Corporate Governance, Operational Costs and Operating Income (BOPO) on the Financial Performance of Non-Cyclicals Consumer Companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This research method uses a quantitative approach with a type of causality research. The data source used in this research in secondary data. The data collection method applied in this research is non-participant observation. The population in this study are non-cyclicals consumer companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sampling technique in this research uses purposive sampling technique by applying sample criteria. Data analysis techniques use descriptive statistical analysis, classical assumption test, multiple linear regression analysis, coefficient of determination ( ), F statistical test and t statistical test. The result of this research show that earning management, independent commissioner, audit committee, board of directors and operational cost and operating income (BOPO) simultaneously have a significant effect on the companies financial performance. Partially earning management has an effect on the companies financial performance, independent commissioner have an effect on the companies financial performance, the board of directors has no effect on the companies financial performance, the audit committee has no effect on the companies financial performance and operational cost and operating income (BOPO) have an effect on the companies financial performance